2008
DOI: 10.1111/j.0906-7590.2008.05457.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling species distributions without using species distributions: the cane toad in Australia under current and future climates

Abstract: Accurate predictions of the potential distribution of range-shifting species are required for effective management of invasive species, and for assessments of the impact of climate change on native species. Range-shifting species pose a challenge for traditional correlative approaches to range prediction, often requiring the extrapolation of complex statistical associations into novel environmental space. Here we take an alternative approach that does not use species occurrence data, but instead captures the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
391
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(414 citation statements)
references
References 47 publications
12
391
0
5
Order By: Relevance
“…Thus, cane toads living in arid environments face strong seasonal selection from temperature and desiccation stressors. Their ability to regulate physiological traits that balance thermal and water homeostasis is essential for survival and range occupancy [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cane toads living in arid environments face strong seasonal selection from temperature and desiccation stressors. Their ability to regulate physiological traits that balance thermal and water homeostasis is essential for survival and range occupancy [25].…”
Section: Discussionmentioning
confidence: 99%
“…Body mass and body length were measured to estimate each individual's hydric state using the residual scores derived from a log mass against log length linear regression model. Because toads can store more than 50% of their mass as water in their bladder, evaporative water loss leads to large changes in daily body mass and is highly indicative of toad hydric state and hence desiccation stress [25][26][27][28]33]. We collected 2 ml of blood following decapitation (less than 1 min).…”
Section: (B) Assessment Of Environmental Stress On Toadsmentioning
confidence: 99%
“…These behaviors may occur at a shorter temporal scale than can be modeled effectively over long durations, and thermal suitability may not be easily represented in correlative procedures. Additionally, the spatial scale at which thermal mechanisms seem to constrain distributions is likely larger than the scope of our study (Kearney et al, 2008;Kearney et al, 2009). The importance of thermal and nutritional constraints on mate-seeking and nesting strategies should not be downplayed, however; rather, at a local spatial scale, our data suggest that these factors may not be easily expressed in a correlative modeling approach or combined with temporally coarser habitat GIS layers .…”
Section: Model Validationmentioning
confidence: 77%
“…Some proponents of process-based models have suggested 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 needed to clearly identify and model axes of the fundamental niche (Kearney and Porter, 2004), whereas others have suggested that focusing solely on the fundamental niche does not provide a complete picture of a species' spatial distribution (Godsoe, 2010) or the underlying biotic interactions that define it. Correlative approaches are not as powerful, explicit, or transferable to novel areas as mechanistic ones (Kearney et al, 2008;Kearney et al, 2009;Bartelt et al, 2010), but for many species they offer a quick, easy, and often robust estimate of occupancy (Tsoar et al, 2007;Barrows et al, 2008;Kharouba et al, 2009;Buckley et al, 2010). Morin and Thuiller (2009) suggested that a more robust estimate of occupancy may be achieved by combining correlative and process-based models, which is the primary aim of this paper.…”
Section: Introductionmentioning
confidence: 98%
“…Há fortes evidências que determinadas espécies tenham mudado o período de seus ciclos de vida durante o ano, bem como suas distribuições espaciais (Kearney et al, 2008;Beaumont et al, 2009;Thomas, 2010;Loyola & Martins, 2011). Isto provavelmente esteja ligado às variações anuais e de longo prazo na temperatura (Sinervo et al, 2010;Chen et al, 2011).…”
unclassified